Aristotelianism and Functional Natural Laws (Culturas Científicas, 2018)
Let “Aristotelianism” be the thesis that necessarily all universals are necessarily instantiated in some object or objects. Many Aristotelians have sustained that natural laws are nomological relations between universals instead of a mere regularity of events. There seem to be cases, though, in which there are natural laws but connecting universals that are not instantiated. Our intuitions about natural laws as nomological relations between universals, then, seem to undercut Aristotelianism. One strategy adopted by Aristotelians has been to suppose that in those cases there are functional laws that ground counterfactual facts about non-instantiated universals. They are not cases where some universal exists although it is not instantiated, but cases about what would have happened if some universals that do not exist, had existed. A functional law is a law that connects directly determinable properties instead of determinate properties. It is argued here that this Aristotelian strategy is incoherent. Aristotelianism requires determinable properties to be grounded on determinate properties, but the strategy requires a relation of grounding in the inverse direction.
Keywords: Natual Laws; Function Laws; Aristotelianism; Determinable Properties; Determinate properties